Handbook of Psychology 2003
DOI: 10.1002/0471264385.wei0403
|View full text |Cite
|
Sign up to set email alerts
|

Mood, Cognition, and Memory

Abstract: The interplay between feeling and thinking, affect and cognition, has been a subject of scholarly discussion and spirited debate since antiquity. Within the past 25 years, the affect/cognition interface has also emerged as one of the most active and rapidly developing areas within psychological science. Two phenomena that have attracted much modern interest are mood congruence—the observation that a given affect state or mood promotes the processing of information that possesses a similar affective tone or val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 79 publications
2
35
0
Order By: Relevance
“…On the other hand, teachers who used background music perceived the music as relaxing and facilitating a positive mood. Other previous studies are supportive of such a stance concerning background music (Hallam et al, 2002;Love & Burns, 2007), such as related to music's power for emotional arousal and release (Egermann et al, 2015;Sims Cecconi-Roberts, 2005) and to influence mood positively (Eich & Forgas, 2003). Further study should examine the real effect of background music on children's play in a classroom setting, in order to find out whether teachers' perceptions of background music is evidence based or overestimated.…”
Section: Implications For Early Childhood Music Educationmentioning
confidence: 88%
See 1 more Smart Citation
“…On the other hand, teachers who used background music perceived the music as relaxing and facilitating a positive mood. Other previous studies are supportive of such a stance concerning background music (Hallam et al, 2002;Love & Burns, 2007), such as related to music's power for emotional arousal and release (Egermann et al, 2015;Sims Cecconi-Roberts, 2005) and to influence mood positively (Eich & Forgas, 2003). Further study should examine the real effect of background music on children's play in a classroom setting, in order to find out whether teachers' perceptions of background music is evidence based or overestimated.…”
Section: Implications For Early Childhood Music Educationmentioning
confidence: 88%
“…Hallam et al (2002), for example, suggested that music's reported effects are mediated by their impact on levels of arousal and emotional state rather than affecting cognition directly. Also, music is reported to induce universal emotional arousal (Egermann, Fernando, Chuen, & McAdams, 2015) and influence mood (Eich & Forgas, 2003;Saarikallio, 2008). In a similar line, Ziv & Goshen (2006) found that background music affected five-to six year-old children's interpretation of stories in terms of emotion, such as happy and sad.…”
mentioning
confidence: 82%
“…For example, there has been evidence suggesting mood may facilitate mood-congruent information recall (e.g., Bower, 1981; Eich and Forgas, 2003; Mayer et al, 1995) and that affective states orient attention toward information, which could explain current feelings (Wyer and Carlston, 1979). Unlike healthy controls, responses by participants in at-risk groups did not show a bias for mood-congruent language, suggesting their mood state might not facilitate recall for similar experiences nor guide attention toward information able to account for positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…Mood-dependent memory, in combination with rehearsal effects, also may help explain why individuals whose negative event was more central to their lives experienced more symptoms of PTSD and depression. According to several studies (Eich & Forgas, 2003;Kihlstrom et al, 2000;Taylor, 1991;Watkins, 2002), individuals with depression tend to retrieve more negative information than individuals with no depression. For individuals with emotional distress, higher rates of retrieval of negative memories would increase rehearsal, and therefore, contribute to higher event centrality of these highly rehearsed negative events.…”
Section: Centrality For Negative Event As a Function Of Distress And mentioning
confidence: 99%